A modified phase change pseudopotential lattice Boltzmann model - Gong, W.; Yan, Y.Y.; Chen, S.; Wright, E. (Elsevier, 2018)
Amongst all the multiphase models in the lattice Boltzmann (LB) community, the pseudopotential model has been the most popular approach due to its simplicity and high-efficiency. Recently a number of liquid-vapour phase change models were also proposed based on the pseudopotential LB model. Our study finds that most of the published pseudopotential phase change models rely on an entropy-based energy equation, while the entropy-based energy equation is derived with the equation of state of ideal gas. That means this entropy-based energy equation is not completely suitable for multiphase ow which applies non-ideal equation of state for the phase separation simulation. Therefore a new phase change LB model is proposed in this work, where an improved pseudopotential multiphase model (Li et al., 2013) and a modified energy equation which is solved in the classical fourth-order Runge-Kutta scheme are coupled in a hybrid scheme. The results show that the numerical simulation can capture the basic liquid-vapour phase change features. The D2 law for droplet evaporation is validated and the square of diameter variation is in good agreement with experimental data. Moreover, the three boiling stages (nucleate boiling, transition boiling and film boiling) are accomplished using the modified model, and the corresponding transient heat fluxes are presented.